Spatial Patterns of Cumulative Hotspots and Their Relationships with Topographical Factors and Land Use in Kanchanaburi Province, Thailand - Sae-ngow, Pornperm; Losiri, Chudech; Sitthi, Asamaporn (Forest and Society, 2024)
The clustering of hotspots represents fires occurring at specific locations across various time intervals, and is an increasingly important interdisciplinary research phenomenon. This article investigates the spatial distribution of cumulative hotspots and their relationships with topographical factors and land use in Kanchanaburi province. Data from the Suomi NPP VIIRS system spanning from 2012 to 2021 were utilized for the analysis of Getis-Ord (Gi*) spatial autocorrelation using Fire Radiative Power values. The analysis included the correlation with topographic data such as elevation, slope, aspect, and overlay with land use data. The results reveal that significant hotspots are concentrated in the districts of Si Sawat, Thong Pha Phum, Sai Yok, Sangkhla Buri, and Mueang Kanchanaburi. The majority of hotspots were statistically insignificant (85%), with hotspots (10%) and cold spots (5%) predominantly occurring in forested and agricultural areas. Hotspots were particularly prevalent in the northern and northeastern regions. Therefore, the utilization of Suomi NPP VIIRS data in conjunction with spatial statistics can identify the occurrence of hotspots and cold spots, aiding in planning and policy-making efforts to mitigate hotspot occurrences.